2001
DOI: 10.1111/j.1524-475x.2001.00019.x
|View full text |Cite
|
Sign up to set email alerts
|

Mother‐Infant Interaction and Maternal Substance Use/Abuse: An Integrative Review of Research Literature in the 1990s

Abstract: Purpose (1) Mother‐infant interaction is crucial for optimal infant development and parenting. In the environment of prenatal substance use/abuse there is potential for both mother and child to present negative interactive behaviors. Recent increased incidence of substance use/abuse by pregnant women in the United States has provoked concern for the infant's outcome in these circumstances. Recent literature does not indicate uniformly dismal outlook for infants born exposed to drugs. In this paper, published r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…These findings provide a synthesis of the literature on the quality of caregiving in substance-misusing mothers and is the first quantitative analysis of caregiving quality in substance-misusing mothers. 9 Overall, the composite effect size based on the meta-analysis of all 24 studies indicated that maternal sensitivity and child responsiveness were higher in mothers who had not used illicit substances. However, we found considerable heterogeneity that limited meaningful interpretation of the results.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…These findings provide a synthesis of the literature on the quality of caregiving in substance-misusing mothers and is the first quantitative analysis of caregiving quality in substance-misusing mothers. 9 Overall, the composite effect size based on the meta-analysis of all 24 studies indicated that maternal sensitivity and child responsiveness were higher in mothers who had not used illicit substances. However, we found considerable heterogeneity that limited meaningful interpretation of the results.…”
Section: Discussionmentioning
confidence: 96%
“…A test for subgroup differences found that the lower estimate of effect size within the matched subgroup was not statistically significant (Q(1) = 2.57, P = .11). Although heterogeneity within the matched subgroup was reduced, it was not statistically significant (Q(9) = 12.19 (9), P = .20; I 2 = 26%) and heterogeneity within the nonmatched subgroup remained high and statistically significant (Q(5) = 36.82 (5), P < .00001; I 2 = 86%).…”
Section: Moderation Analyses To Identify Sources Of Heterogeneitymentioning
confidence: 91%
See 2 more Smart Citations
“…In turn, the presence of childhood maltreatment, trauma, and psychopathology coupled with substance misuse is associated with parenting deficits (19). Research further suggested that parents who are substance-involved exhibit different parenting behaviors than those who are not substance-involved, with such differences varying with the characteristics of parents' current drug use (see (20) and (21) for reviews). For example, parents who are substance-involved are more likely to exhibit greater parenting stress (22), decreased attentiveness and engagement with their children (23), more authoritarian parenting (24), and dysfunctional or harsh disciplinary practices (25).…”
Section: Neurobiology Of Parenting and Substance Usementioning
confidence: 99%